PSYCHOEMOTIONAL CHANGES IN PATIENTS AFTER GYNECOLOGICAL OPERATIONS (World Bulletin of Management and Law, 2024)
The review describes in detail the main neurological disorders that develop after hysterectomy: chronic postoperative pain, traumatic neuroma and residual ovarian syndrome as possible causes of chronic pain, mononeuropathy, sexual function and sleep disorders, decreased cognitive and motor functions, lower urinary tract dysfunction and intestines. A significant place is devoted to the mechanisms of development of neurological complications and the relationship of surgery with disturbances of the emotional background in women.